Exporter Exposure to Indonesia’s 2026 Rice Import Ban: Evidence from Trade Concentration and Dependence Ratios - Chayutrakorn, Chalita; Sari Supriyanti, Ratna; Tubpond, Teerapong (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The Indonesian government has announced a suspension of rice imports starting in 2026, marking a shift away from its historical reliance on imports to stabilize domestic supply and prices. Using annual data from 2017–2024, this study applies descriptive statistics, high- and low-import year comparisons, correlation analysis between import volumes and import unit values (IUV), and Exporter Dependence Ratios (EDR) to assess exporter exposure to the loss of the Indonesian market. Results show that imports are highly volatile but increasingly concentrated, with Thailand and Vietnam dominating recent high-import periods, while India, Pakistan, and Myanmar display more variable participation. High EDR values for Myanmar, Thailand, and Vietnam indicate substantial dependence on Indonesian demand. The findings suggest that the 2026 import ban may create significant adjustment pressures for these exporters while removing a key external mechanism that previously helped stabilize Indonesia’s domestic prices.